ELECTRON-PARAMAGNETIC RESONANCE OF SPIN-CORRELATED RADICAL PAIRS IN PHOTOSYNTHETIC REACTIONS - Hore, P; Hunter, D; Mckie, C; Hoff, A (1987)
Previous attempts to interpret the time-resolved electron paramagnetic resonance spectra of photosynthetic bacteria have been based on the premise that electron spin polarization arises in the primary radical pair (P+I- fromed by photoinduced charge separation. The observed spectrum is assumed to be the sum of the EPR spectra of P+ and X-, the radical produced from I- by electron transfer. Here it is argued that P+I- may be too short-lived to give rise to significant polarization and that the experimental spectrum is consistent with the rapid formation of a spin-correlated secondary radical pair. © 1987.